Pengaruh Inflasi, Nilai Tukar, Suku Bunga dan Produk Domestik Bruto terhadap Return Saham pada Perusahaan Manufaktur - Rini Hastuti; Irawan Irawan; Alexandra Hukom (Studi Ekonomi dan Kebijakan Publik, 2023)
Purpose: To find out whether the Gross Domestic Product, the exchange rate, and the interest rate of the Gross Domestic Product together affect the stock returns of manufacturing companies. Methodology: This study uses quantitative methods and secondary data. The scope of this research relates to data on manufacturing companies listed on the Indonesia Stock Exchange in 2017 - 2019. Results: The results of multiple linear regression analysis show that GDP growth, inflation, interest rates, and the Indonesian rupiah exchange rate have an influence on stock returns on the Indonesia Stock Exchange. On the other hand, some exchange rates have a negative effect on stock returns. In addition, inflation also has a large partial negative effect on stock returns, but interest rates have a partially positive effect on stock returns. Limitations: Only tested 4-factor variables that affect stock returns in a certain period. Contribution: It is hoped that this research can be useful for investors who will invest in certain manufacturing business sectors to be more careful in paying attention to various factors that affect stock returns.